Studies of H-Mg and H-Ca Exchanges on Acrylic Carboxylic Cationites from the Viewpoint of the Exchange Equilibrium Theory - A.V. Mamchenko; E.A. Valuiskaya; G.V. Klimova (Adsorption Science & Technology, 2000)
The sorption of Mg 2+ and Ca 2+ ions by the H-form of the acrylic carboxylic cationite Lewatit CNP 80 as the magnesium sulphate or calcium chloride concentration in the external solution was varied by two orders of magnitude has been considered from the viewpoint of the ion-exchange equilibrium theory. The experimental data were obtained using a method which provided high precision measurements of the potentiometric titration curve over a wide range of resinate compositions for the ionite gel phase. The strong dependence of the effective equilibrium constant on the resinate solution composition was described satisfactorily by the exchange equilibrium theory. The selectivities towards Ca 2+ and Mg 2+ ion sorption by the H-type of carboxylic cationite studied were close. An explanation for this phenomenon was proposed.